1977
DOI: 10.1029/gl004i006p00239
|View full text |Cite
|
Sign up to set email alerts
|

Deep crustal electrical conductivity; Evidence for water in the lower crust

Abstract: Controlled source magnetic induction experiments in the Adirondack Precambrian shield region of northern New York State indicate that the electrical conductivity in both the upper and lower crust are in conformity with laboratory studies of moist, igneous rock and in serious discord with such measurements on dehydrated rock. A two order of magnitude increase in the conductivity found at 20 km depth suggests a structural or phase change there. A single turn loop of wire 1.5 km in diameter was used to generate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Without repeating all the arguments, the evidence for a water-filled, interconnected pore space seemed compelling at least to about 5 km. Recent deep resistivity measurements [Nekut et al, 1977] suggest that the same conclusion holds to 20 km, and a recent study of crustal permeability argues for high conductivities to 8 km [Brace, 1980]. High fluid conductivity necessitates interconnecting fractures, since porosity in crystalline terrains must be a percent or less.…”
Section: Brittle Fracturementioning
confidence: 99%
“…Without repeating all the arguments, the evidence for a water-filled, interconnected pore space seemed compelling at least to about 5 km. Recent deep resistivity measurements [Nekut et al, 1977] suggest that the same conclusion holds to 20 km, and a recent study of crustal permeability argues for high conductivities to 8 km [Brace, 1980]. High fluid conductivity necessitates interconnecting fractures, since porosity in crystalline terrains must be a percent or less.…”
Section: Brittle Fracturementioning
confidence: 99%
“…Laboratory experiments show that most rocks experience significant hydraulic weakening when exposed to water. There is ample evidence to suggest that crustal theologies in seismogenic zones are wet [e.g., Brace, 1972;Nekut et al, 1977;Brace, 1980]. (3) Dry feldspar aggregates are considered.…”
Section: /;= a Tj N Exp(q/rt) (6)mentioning
confidence: 99%
“…Nekut et al (1977) suggested that in the crystalline rocks of the Adirondacks a water-filled pore space to a depth of 20 km is required to explain the relatively high electrical conductivity of the crust. Permeabilities inferred from earthquake mi-gration and other large-scale crustal phenomena ranges (Brace, 1980;, for crystalline rocks, from 10-12 to 10-1°CM2 which are about the same as the more permeable intervals in boreholes.…”
Section: Methodsmentioning
confidence: 99%